Importancia económica de las características fonéticas del idioma espa\~nol y sus variedades regionales - Germán Coloma (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2010)
– This paper tries to quantify economically the importance of five phonetic haracteristics (seseo, yeismo, /s/-aspiration, rehilamiento, and /x/-aspiration) whose presence or absence allows to distinguish among ten regional varieties of Spanish. To do that we perform an analysis of the extension of those characteristics and we estimate which of them correspond to the average speaker of Spanish, which end up being identical to the ones of the so-called modern Andean Spanish. Through estimations of per capita income, however, we find that the characteristic associated with a higher income level is the absence of seseo, typical of the Northern Peninsular Spanish. Finally, through a statistical regression analysis, we find that such characteristic is associated with an average annual per capita income which is US 24,500 higher than the one of Spanish speakers that possess seseo. We also find that the only additional characteristic that is statistically significant as a signal of a higher income is rehilamiento, which is associated with an average annual per capita income that is US 4,500 higher than the one of speakers that do not possess that characteristic.
Keywords: 330; phonetic characteristics; Spanish regional varieties; average speaker; per capita income; statistical regression; características fonéticas; variedades regionales del espa\~nol; hablante promedio; ingreso per cápita; regresión estadística